Assessment of Loan Repayment Capacity of Cooperative Farmers in Bayelsa State, Nigeria - Ilavbarhe, K. O.,; Alufohai, G. O.; Keyagha, T. S. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2017)
The study assessed loan repayment capacity of cooperative farmers in Bayelsa State between 2009 and 2014. It specifically examined the socio-economic profile of the cooperative farmers, estimated the rate of loan repayment by borrowers and determined the loan recovery strategies of the farmers’ cooperatives societies. A multistage sampling technique was used to select 200 respondents in the study area. Structured questionnaire and interview schedule were used to obtain data from the respondents. Data were analyzed using percentages, means, multiple regression, loan repayment indices, t-test and F-test. The result showed that 80% of the loans granted to the beneficiaries were repaid back while 19.84% of the borrowers had their loan outstanding. Farm size and years of cooperative membership were found to have a positive effect on loan repayment capacity. The amount of loan received and net farm income recorded positive t-value and was statistically significant. It was recommended that farmers be encouraged to join cooperative societies so as to take advantage of economies of scale.